Knowledge translation: Radiographers compared to other healthcare professionals. (October 2020) - Di Michele, L.; Thomson, K.; McEntee, M.F.; Kenny, B.; Reed, W.
Abstract: Objectives: This narrative review examines the current status of evidence-based practice and knowledge translation in diagnostic radiography. It explores knowledge translation efforts in the allied health professions aimed at systematically implementing evidence-based practice and suggests ways that these may be applied within diagnostic radiography. Key findings: Knowledge translation in diagnostic radiography is in its infancy with numerous examples of key findings of rigorous studies not implemented in practice. Utilising frameworks, models and theories to systematically translate knowledge into evidence-based practice has been shown to be effective in other allied health professions. Whilst few studies in diagnostic radiography report utilising these systematic approaches to implementing evidence-based practice, those that do, show promising results. Attitudes towards evidence-based practice within diagnostic radiography are becoming more positive and it is important to use this positive shift in attitudes to create real evidence-based change in the profession. Conclusion: The potential benefits of systematically translating knowledge into evidence-based practice in diagnostic radiography are wide reaching with positive implications for our patients, the profession and wider community. Leaders at all levels of radiography must work towards implementing evidence-based practice in their daily work. Implications for practice: Systematic approaches to knowledge translation should be adopted and reported in diagnostic radiography in order to more effectively translate knowledge into evidence-based practice.